PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DANA PURNA INVESTAMA JAKARTA PUSAT - Herwan Siburian; Moh. Jazuli (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work motivation and work discipline on employee performance both partially and simultaneously at PT. Central Jakarta Purna Investama Fund. The research method that will be used in this research is an associative method with a quantitative approach, using a saturated sample with a population of all PT employees. Central Jakarta Purna Investama Fund. as many as 60 respondents. The analytical methods used in this research are simple and multiple linear regression analysis, analysis of the coefficient of determination R2, and hypothesis analysis of the t test (partial) and f test (simultaneous). Based on the research results, work motivation has a significant effect on employee performance with the regression equation Y 38.291 + 0.050 X1. Hypothesis testing obtained t calculated t table or (0.447 < 1.671). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant influence between motivation and employee performance. Work discipline has a significant effect on employee performance with the regression equation Y 18.389 + 0.556 X2. Hypothesis testing obtained t calculated t table or (4.861 > 1.671). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant influence between work discipline on employee performance. Work motivation and work discipline have a significant effect on employee performance with the regression equation Y 14.578 + 0.087 X1 + 0.565 X2. The coefficient of determination value is 30.0% while the remaining 70% is influenced by other factors. Hypothesis testing obtained a calculated F value of F table or (12.215 > 4.00). Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between work motivation and work discipline on employee performance at PT. Central Jakarta Purna Investama Fund